Factors influencing visitors' perception on congestion in Giant Panda Conservation Centre (GPCC), Zoo Negara - Lim, Sin Yun (2016)
Giant Panda Conservation Centre (GPCC) is one of the significant attractions in Zoo Negara. The arrival of Giant Pandas (Fu Wa) Xing Xing and (Feng Yi) Liang Liang in 21 May 2014 symbolizes the 40th anniversary of Malaysia-China diplomatic ties which attract worldwide lens attention. Besides that, there is a significantly increase of the total number of visitors after the panda cub (Nuan Nuan) was release to public in 17 November 2015. The increasing number of visitors has created some impacts such as crowdedness to the site and facilities. Therefore the factors affecting visitors’ perception on acceptable level of congestion in GPCC must be determined. Besides that, it also aimed to study the socio-demographic variables in GPCC. The variables were measured using a four points Likert scale through questionnaire survey of 250 respondents. The result shows the respondents were acceptable to the congestion condition in GPCC. The highest acceptable level toward congestion condition was obtained by the information center in GPCC which is the area where visitors enter after the entrance while the lowest acceptable level toward congestion condition was obtained by the zoovenir shop, which is the souvenir shop in GPCC.Besides, visitors’ overall acceptable level toward congestion was affected by the method of visitors choose to reach GPCC; visitors get the source of information from brochures, magazine and newspaper and secondary education level. In conclusion, the management should not neglect the acceptable level of visitors toward the congestion problems because it will affect the intention of visitor to revisit the zoo.